Pengaruh Tingkat Pengetahuan Orang Tua Terhadap Penyakit Pneumonia Dan Pemberian Imunisasi Pneumocuccal Conjugate (PCV): The Influence of Parental Knowledge Level on Pneumonia Disease and Pneumococcal Conjugate (PCV) Immunization - Sari, Ambar (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Pneumonia is an infection or acute inflammation of the lung tissue caused by various microorganisms, such as bacteria, viruses, parasites, fungi, exposure to chemicals, or physical damage to the lungs. Pneumonia usually affects children, but it can be prevented by vaccine PCV. Based on the above, researchers are interested in conducting a study entitled “Influence Level Of Parental Knowledge Of Pneumonia And Immunization Pneumococcal Conjugate (PCV) In Integrated Healthcare Center Camelia.” Objective: Knowing the influence level of parental knowledge of pneumonia and immunization pneumococcal conjugate (PCV) in Integrated Healthcare Center Camelia.” Methods: The study used cross-sectional and purposive sampling with a sample of 36 people. Data techniques are included in univariate analysis using frequency distribution and bivariate analysis using statistical calculations of SPSS programs. Results: Results showed that there was a significant level of parental knowledge of pneumonia, with p-value (0,026) < α (0,05) showing that there were significant differences in the level of parental knowledge of pneumonia. and immunization pneumococcal conjugate (PCV). Discussion: There is a significant influence on the level of parental knowledge of pneumonia and immunization pneumococcal conjugate (PCV). It is hoped that it will increase the knowledge of parents so that the coverage of immunization completeness is fulfilled, especially PCV immunization.